GESTÃO DO FUTEBOL PROFISSIONAL NO RIO AVE F.C., FUTEBOL SDUQ LDA. - ESTÁGIO PROFISSIONALIZANTE - João Pedro Santos Silva (2017)
This Internship Report is the result of the internship held during the 2nd year of the 2nd cycle of studies in Sports Management of the University of Porto's Sports Faculty, which took place at the Rio Ave Futebol Clube - Futebol SDUQ, Lda. and July 2017. During the mentioned period, it was in accordance with the participation in two competitions recognized as professionals, being the main the national champion of the 1st division - League NOS - and the league cup - denominated Cup CTT. The opportunity was the result of institutional contacts between the Management of the 2nd cycle in Sports Management of FADEUP and the SDUQ in question, namely between Prof. Maria José Carvalho and Dr. Miguel Ribeiro - general director of Rio Ave. From the when it became possible the effectiveness of the internship depended on me seizing the opportunity, working hard and showing my worth. Over the time that I went through the internship I was able to acquire several knowledge and skills that allow me to be more prepared to face the labor market. From the outset it allowed me to perceive the organization and functioning of a structure of a sports society with the size of Rio Ave. After the end of the internship and the preparation of this same report, it was possible to see the importance that is increasingly attributed to Sports Management for the proper functioning of professional structures in the world of football.